Application of analytical hierarchy process (AHP) in generating land suitability index (LSI) for sugarcane in Central Mindanao, Philippines - Alburo, Jim Loui P.; Garcia, Jose Nestor M.; Sanchez, Pearl B.; Sta. Cruz, Pompe C. (2019)
Sugarcane is one of the most promising industry in the Philippines and planted in any land in the country...